2011
DOI: 10.4021/jocmr581w
|View full text |Cite
|
Sign up to set email alerts
|

Dubowitz Syndrome: A Review and Implications for Cognitive, Behavioral, and Psychological Features

Abstract: Dubowitz syndrome is a rare autosomal recessive disorder characterized by micorcephaly, short stature, abnormal faces, and mild to severe mental retardation. Growth retardation occurs both intrauterine and postnatal. Behavioral characteristics include hyperactivity, short attention span, and aggressiveness. Behavior problems include difficulty feeding, sleep disturbance, and bedwetting. Individuals with the disorder have displayed shyness, fear of crowds, and dislike of loud noises. A high-pitched or hoarse vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 35 publications
0
28
0
3
Order By: Relevance
“…Next, using the secondary keyword search (hereinafter: see Methods: Additional file 2: Figure S1: one box outlined with a dotted line), we found the retrospective and clinical case reviews indicating that short stature and aggressiveness coexist in Smith-Magenis syndrome [71, 72], Dubowitz syndrome [73], and Floating-Harbor syndrome [74]. In addition, women of constitutionally short stature are more aggressive than the ones with Turner syndrome [75].…”
Section: Resultsmentioning
confidence: 99%
“…Next, using the secondary keyword search (hereinafter: see Methods: Additional file 2: Figure S1: one box outlined with a dotted line), we found the retrospective and clinical case reviews indicating that short stature and aggressiveness coexist in Smith-Magenis syndrome [71, 72], Dubowitz syndrome [73], and Floating-Harbor syndrome [74]. In addition, women of constitutionally short stature are more aggressive than the ones with Turner syndrome [75].…”
Section: Resultsmentioning
confidence: 99%
“…Dentro de los principales síndromes asociados con talla baja e historia de peso bajo al nacer se encuentra el síndrome de Dubowitz, entidad autosómica recesiva de la que han sido descritos aproximadamente 200 casos y que no tiene predilección étnica o de sexo 33 . Esta patología es el principal diagnóstico diferencial del SSR ya que comparten varias características clínicas: RCIU, retraso en el crecimiento posnatal, micrognatia, apiñamiento dental, anomalías de pabellones auriculares, alteraciones genitourinarias y voz aguda.…”
Section: Discussionunclassified
“…Esta patología es el principal diagnóstico diferencial del SSR ya que comparten varias características clínicas: RCIU, retraso en el crecimiento posnatal, micrognatia, apiñamiento dental, anomalías de pabellones auriculares, alteraciones genitourinarias y voz aguda. Adicionalmente presenta cara triangular, asimetría facial, ptosis (65%) y alteraciones genitourinarias 33,34 . En este estudio, en uno de los pacientes en quien se descartó SSR, se integró el diagnóstico de sín-drome de Dubowitz, ya que el paciente solo contaba con dos criterios mayores para SSR (peso bajo para la edad gestacional, peso y talla bajos posnatales < P3) y presentó además datos no consistentes con SSR y sí asociados con el síndrome de Dubowitz, como microcefalia, bicitopenia, infecciones en vías urinarias recurrentes y alergias alimentarias, además de un fenotipo facial compatible.…”
Section: Discussionunclassified
“…The direct cause of the disorder is still unknown; however, most of the published data refer to possible genetic etiology 2. Indeed, a recent study has reported the NSUN2 gene as the first potential causal gene with a relationship to the Dubowitz syndrome spectrum phenotype 10…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Dubowitz syndrome is known to be associated with other medical problems that increase the risk for a shorter life span. Although Dubowitz syndrome has been well described in the literature since it was first identified in 1965, the exact cause of this disorder is still unknown and diagnosis is based mainly on clinical features 25…”
Section: Introductionmentioning
confidence: 99%